The Wisdom of Polygamy of Prophet Muhammad SAW: An Examination of the Interpretation of Ali Al-Shabuni in the Book of Rawai' al-Bayan Tafsir Ayat al-Ahkam - Rusdi, Hilda Husaini (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
This article aims to find out the wisdom of the Prophet Muhammad's polygamy according to Ali al-Shabuni in his book Rawai' al-Bayan. This is based on the fact that there are different perspectives where polygamy is considered a negative action. Apart from that, polygamy is also alleged to be an act that can hurt women and only favors men. However, Islam allows polygamy on condition that the husband can treat all his wives fairly. This refers to the QS explanation. al-Nisa' [4]: ​​3 which is seen as an argument for the legalization of polygamy. By using a qualitative-descriptive method, this article concludes that: First, Ali al-Shabuni views marriage as a form of sunnah, while for men who are polygamous with more than four wives it is forbidden. In other words, al-Shabuni allows polygamy as long as it meets the terms and conditions set by Islam. Second, the polygamous marriage practiced by the Prophet Muhammad according to Ali al-Shabuni contains four lessons that deserve attention, namely the teaching aspect, the legal aspect, the social aspect and the political aspect. From the four wisdoms mentioned by al-Shabuni, it appears that the Prophet's goal of polygamy was for the sake of religion and explaining religious law, especially to subdue the hearts of human opponents so that they could be attracted to embrace Islam and be able to establish good relations. In each of his marriages, the Prophet showed concrete evidence indicating his intelligence and courage, the height of his ideals and the beauty of his behavior. The Prophet's marriage was also not based on the satisfaction of sexual desire, because the Prophet when he was polygamous was not in his teens and the ones he married were not even girls.